2017
DOI: 10.1002/gps.4648
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of people with dementia and their carers participating in individual cognitive stimulation therapy

Abstract: People with dementia and their family carers found iCST stimulating and enjoyable, but many had difficulty delivering all the sessions as planned. Family carers suggested that providing extra support by involving other people in delivering the intervention may help to improve adherence to the intervention. iCST may be a useful tool to encourage people with dementia and their carers to communicate. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 38 publications
1
69
0
1
Order By: Relevance
“…Seven studies employed purely qualitative design (Aguirre, Spector, Streater, Burnell & Orrell, 2011;Bertrand et al 2018;Dickinson, Gibson, Gotts, Stobbart & Robinson, 2017;Leung, Yates, Orgeta, Hamidi & Orrell, 2017;Spector, Gardner & Orrell, 2011;Streater, 2015;Yates et al 2015). Three studies used mixed methodology (Bailey, Kingston, Alford, Taylor & Tolhurst, 2017;Kelly et al 2017;Wong, Yek, Zhang, Lum & Spector, 2018).…”
Section: Quality Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Seven studies employed purely qualitative design (Aguirre, Spector, Streater, Burnell & Orrell, 2011;Bertrand et al 2018;Dickinson, Gibson, Gotts, Stobbart & Robinson, 2017;Leung, Yates, Orgeta, Hamidi & Orrell, 2017;Spector, Gardner & Orrell, 2011;Streater, 2015;Yates et al 2015). Three studies used mixed methodology (Bailey, Kingston, Alford, Taylor & Tolhurst, 2017;Kelly et al 2017;Wong, Yek, Zhang, Lum & Spector, 2018).…”
Section: Quality Analysismentioning
confidence: 99%
“…However, additional necessary resources were highlighted, including people, time, and physical resources such as equipment and rooms needed to run sessions (Dickinson et al 2017;Kelly et al 2017). Appropriate communication skills, and support from others was also seen as very important both by professionals and family carers delivering the intervention (Streater et al, 2015;Leung et al 2017). Further, carers wondered if iCST would be best delivered by professionals or an "outsider" (Yates et al 2015).…”
Section: Facilitators and Barriersmentioning
confidence: 99%
“…Fidelity of delivery and engagement are complex behaviours with many underlying mechanisms. For example, environmental, organisational and individual characteristics have been found to influence fidelity of, and engagement with dementia interventions and interventions in general [9][10][11][12][13][14][15][16][17][18]. To understand how an intervention is implemented, the Medical Research Council (MRC) guidance [8], together with previous research [15,19] propose that mixed methods evaluations of interventions are needed to provide a detailed understanding of intervention functions.…”
Section: Introductionmentioning
confidence: 99%
“…A recent randomized, controlled trial of iCST showed that iCST did not result in improved cognition or quality of life for the person living with dementia, however, participating in iCST did enhance the quality of the caregiving relationship and caregivers’ quality of life. 23 , 24 These findings are relevant here, as companions of people with PRD are reported to experience burden and a lower quality of life due to the responsibility of supporting the complex physical and cognitive needs of people with PRD. 25 We are aware of only one exploratory study 26 that has assessed the effectiveness of home-based CST in people with PRD using neuropsychological assessment and molecular analysis.…”
Section: Stage 1 – Summarize and Review (Existing Research)mentioning
confidence: 86%